EDUKASI KEPADA MASYARAKAT TENTANG PEMANFAATAN PEKARANGAN RUMAH DENGAN TANAMAN OBAT KELUARGA (TOGA) - I Kadek Wartana; Gustini Gustini; Saiful A; Desak Eka Susianawati; Ida Yanriatuti; Lexy Kareba; Agustinus Talindong; Fitriani Dafer; Ni Kadek Armini (Universitas Negeri Medan, 2023)
The widespread counterfeit circulation and the increasing price of medical drugs in the market can be overcome by using family medicinal plants. However, the yards utilization is still low, so education is needed to make people understand the benefits of family medicinal plants. The aim of this community service was educated the public about the importance of planting family medicinal plants. The method was educated about the importance of planting family medicinal plants and made demonstration gardens. This activity was carried out on Tuesday-Saturday March 14-18, 2023. The target was 20 householders in Rogo Village. The results were an increase in participants' knowledge about the meaning, types and benefits of family medicinal plants for treating diseases and the availability of demonstration gardens in each hamlet. The conclusion was that providing education to the community can increase their knowledge about the importance of using family medicinal plants in their yards.Â